Identification of Candida Species Associated with Vulvovaginal Candidiasis by Multiplex PCR. (26th June 2012) - Mahmoudi Rad, Mahnaz; Zafarghandi, Ameneh Sh; Amel Zabihi, Maryam; Tavallaee, Mahkam; Mirdamadi, Yasaman
Abstract : Background . Vulvovaginal candidiasis is a common infection. The aim of this study was to identify the species of vaginal Candida isolates by using multiplex PCR technique. Methods . 191 isolates from patients admitted to Mahdieh hospital were identified. The vaginal swab specimens were cultured on Sabouraud Dextrose Agar. The ITS1 region between the 18S and 5.8S rRNA genes and a specific DNA fragment within the ITS2 region were amplified. The multiplex PCR products were separated by electrophoresis in 2% agarose gel, visualized by staining with ethidium bromide, and photographed. Descriptive statistics, Chi-square test, and Spearman correlation were used to summarize the findings. Results . C. albicans and C. glabrata were the most common species isolated from the specimens. A mix of C. glabrata and C. albicans was the most common mixed infection isolated from the samples. The analysis revealed a significant positive association between older age and infection with C. glabrata isolates (Spearman's rho = 0.89, P = 0.015 ). Conclusion . Multiplex PCR is a fast, yet reliable method to identify Candida species. C. albicans and then C. glabrata are the two most common causes of vulvovaginal candidiasis. The number of mixed fungal infections is higher among Iranian population compared to international reports.